Incorporating the Clinical Frailty Scale into routine outpatient nephrology practice: an observational study of feasibility and associations. Issue 8 (22nd August 2021) - Kumarasinghe, Anuttara Panchali; Chakera, Aron; Chan, Kien; Dogra, Sharan; Broers, Sally; Maher, Sean; Inderjeeth, Charles; Jacques, Angela
Abstract: Background: There is an unmet need for routine and accurate prognostication of older adults with end‐stage kidney disease (ESKD) and subsequently inadequate advance care planning. Frailty, a clinical syndrome of increased vulnerability, is predictive of adverse health outcomes in the renal population. We propose the Clinical Frailty Scale (CFS) as a feasible tool for routine use in the nephrology outpatient setting to address this unmet need. Aims: To assess feasibility and associations of incorporating CFS assessment into routine outpatient nephrology practice in the pre‐dialysis setting. Methods: CFS was integrated into the outpatient nephrology clinic proforma. A convenience sample of 138 patients aged >50 years, with estimated glomerular filtration rate (eGFR) <30 mL/min/1.73 m 2, attending the outpatient service between September 2018 and April 2019 was included. Results: Eighty‐one CFS assessments were completed by nephrologists, nephrology advanced trainees and clinical nurse specialists. CFS completion rates were 79% from the multidisciplinary Low Clearance Clinic and 41% from nurse‐led Pre‐dialysis Education Clinic. Planned modality of ESKD management varied with degree of frailty ( P < 0.001). 21% of patients who had CFS completed were planned for Conservative Management of ESKD, in contrast to only 5% of those who did not have CFS assessment completed ( P < 0.001). Conclusion: Frailty assessment via CFS was feasible in outpatient practice when integrated into routine clinical assessment in a dedicated clinic. Planned ESKD management varied with the degree of frailty. Completion of frailty assessment, when compared with non‐completion, appears to be associated with increased planned conservative management of ESKD.